Islamic Education In Montongsari Village: A Case Study Of Educational Materials From The Perspective Of The Quran And Hadith - Nurul Hidayah; Ahya Nur Annisa’; Rizca Wulandari; Ulin Nihayah (Universitas Palangka Raya, 2024)
This research aims to explore the implementation of Islamic education materials in Montongsari Village from the perspective of the Qur'an and Hadith. Islamic education plays an important role in shaping people's character and faith, especially in villages with strong traditional values. This study uses a qualitative approach with a case study method, which involves participant observation and document analysis. Based on the results of the discussion, it is concluded that educational materials in Montongsari Village are very important to be taught to students as stated in the verses of the Qur'an and hadith, including Islamic religious education, exact social sciences, aqidah, fiqh, Al-Qu'ran and worship. Education in Montongsari Village has shown success in implementing comprehensive Islamic religious material. Although there are many challenges, Montongsari Village educators have many alternatives so that challenges can be overcome. For example, using teaching aids, digital media such as videos and the internet can attract students. Better integration between technology and religious teaching is expected to improve the quality of Islamic religious education in the village